PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN TELEKOMUNIKASI DENGAN COVID-19 SEBAGAI VARIABEL CONTROL - Pramudianto, Chori Baskoro; Eko Waluyo, Dwi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The purpose of this study was to determine and analyze the effect of profitability, liquidity, capital structure and solvency on the value of telecommunications companies listed on the Indonesia Stock Exchange for the 2019-2022 period with covid-19 as a control variable. The data used is secondary data from the company's financial statements. This study applied purposive sampling technique in sampling, obtained a sample of 8 telecommunications companies with 128 financial reports. This study applies quantitative methods using data analysis techniques, namely panal data regression analysis and using eviews 12 for data processing. From this study, the results obtained based on the t statistical test, firm value does not get a partially significant positive effect from profitability, liquidity, and firm value does not get a partially significant negative effect from solvency, but firm value gets a partially significant negative effect from capital structure and covid-19. Based on the f statistical test, the company value gets a significant effect simultaneously from profitability, liquidity, capital structure, solvency and covid-19.